2002
DOI: 10.1197/aemj.9.12.1397
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Triage Assessments among Pediatric Registered Nurses and Pediatric Emergency Physicians

Abstract: Objectives:To compare triage level assignments, using simulated written case scenarios, in a pediatric emergency department (ED) among registered nurses (RNs) and pediatric emergency physicians (PEPs) and to compare the triage level assignments among RNs and PEPs with a consensus criterion standard. Methods: This was a cross-sectional mailed questionnaire survey. The study was conducted at a pediatric tertiary care center with more than 65,000 annual patient visits. Participants were PEPs and RNs working in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…4,11,12 Few studies have evaluated the reliability of triage tools for children. 10,[13][14][15][16] Interrater agreements in these studies varied, with kappa scores ranging from 0.26 to 0.55. All these studies were based on case scenarios rather than a clinical setting.…”
mentioning
confidence: 97%
“…4,11,12 Few studies have evaluated the reliability of triage tools for children. 10,[13][14][15][16] Interrater agreements in these studies varied, with kappa scores ranging from 0.26 to 0.55. All these studies were based on case scenarios rather than a clinical setting.…”
mentioning
confidence: 97%
“…Finally, previous studies reported agreement varying from 53% to 64% between triage nurses assigning a triage level to written case scenarios when compared with a panel of 3 experts. 10,12,13 Other triage tools have also demonstrated strong association between triage levels and markers of clinical severity for children. In 2005, Baumann and Strout 19 reported a high correlation between triage levels assigned by nurses using the Emergency Severity Index and hospital admission rate, resources use and LOS in the ED among 510 children visiting an ED.…”
Section: Casementioning
confidence: 99%
“…The "urgency" of a clinical situation can be relatively subjective. Previous studies have evaluated the validity of triage tools by comparing the triage level of live patients or case scenarios with either a panel of experts, 10,[12][13][14][15] or hospital admissions or resources used. [16][17][18][19] These later studies have suggested that admission to hospital, length of stay (LOS) in the ED and resources use are appropriate proxy markers for patient severity.…”
Section: Introductionmentioning
confidence: 99%
“…These studies used the same case scenarios as the present study and were performed in the same ED in 2000 and 2002. 21,22 The k scores for these previous studies ranged from 0.45 to 0.51 for the nurses and from 0.39 to 0.42 for the physicians. The agreement reported in the present study (k scores, 0.51 and 0.55) is higher than previous evaluations of the same case scenarios in the same setting.…”
Section: Discussionmentioning
confidence: 95%
“…The same scenarios have been utilized in previous studies. 21,22 The nurses were not allowed to take notes regarding the case scenarios and were asked not to discuss the cases among themselves.…”
Section: Study Protocolmentioning
confidence: 99%